Treatment Options in Metastatic Renal Cell Carcinoma: Focus on mTOR Inhibitors - Pal, Sumanta Kumar (Libertas Academica, 2010)
The agents currently approved for use in metastatic renal cell carcinoma (mRCC) can be divided broadly into two categories: (1) vascular endothelial growth factor receptor (VEGFR)-directed therapies or (2) inhibitors of the mammalian target of rapamycin (mTOR). The latter category includes everolimus and temsirolimus, both approved for distinct indications in mRCC. Everolimus gained its approval on the basis of phase III data showing a benefit in progression-free survival relative to placebo in patients previously treated with sunitinib and/or sorafenib. In contrast, temsirolimus was approved on the basis of a phase III trial in treatment-naïve patients with poor-risk mRCC, demonstrating an improvement in overall survival relative to interferon-alfa. While these pivotal trials have created unique positions for everolimus and temsirolimus in current clinical algorithms, the role of mTOR inhibitors in mRCC is being steadily revised and expanded through ongoing trials testing novel sequences and combinations. The clinical development of mTOR inhibitors is outlined herein.